Effects of Lottery Wins on Household Labor Supply - Ignacio Belloc; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2023)
This paper analyses the impact of current and past lottery wins on household labor supply in the United Kingdom using data from the British Household Panel Survey 1997-2008. Estimating individual fixed-effects models, we show that male annual hours of work do not respond to lottery wins, whilst female hours of work decrease in response to current and past lottery wins. Specifically, current female annual hours of work decrease by about 26 hours if the partner has won the lottery during that year, and about 28 hours per year if he won the lottery the previous year. When we include large lottery wins (lottery wins worth more than 500), we find a compensation effect within the household, as the recipient's spouse increases his/her hours of work. These results are inconsistent with household unitary models, and suggest that large shocks in unearned income may have a persistent impact on household behavior.
Keywords: D13; D31; J22; 330; household labor supply; lottery win; fixed-effects models; British Household Panel Survey